Determination of Hydrodynamic Activity of Ground Water for Um Er Radhuma Aquifer in Al-Salman District, Southern Iraq - Shahad Al-Qaraghuli (Indonesian Journal Publisher, 2025)
Six wells’ samples were collected from Umm Er Radthuma aquafer distributed in the region in Al-Salman district, Al-Muthana governorate in the southern part of Iraq during November 2024 and it’s compared with four wells samples collected from the same region during year 2010. Umm Er Radhuma formation is represented the major aquifers and the type is a confined aquafer. The samples of ground water were examined for major cations and anions, PH, total dissolved solids (TDS) and electrical conductivity (EC). The hydro-chemical analysis results obtained from the examined ground water samples are generally alkaline, very hard water, classified a brackish water and the excessively mineralized water. The concentration of anions and cations in the water samples indicate the dominant of Sodium ion in the cations, while the sulphate was the main anion for year 2024 and chloride anion for the year 2010 with increase all the anions and cations values during 2024. The ground water wells are a continental origin except well 3 is marine origin. Therefore, Bojarski method application shows that the all-wells samples have high hydrodynamic activity so that the hydro-carbonic accumulation is a low except well 3 have a low hydrodynamic activity and the hydrocarbon accumulations were high effect. The water type according to Kurolov formula is Na2SO4 in the most wells except well 3 is NaCl. The ground water of Al- Salman region has indicated that the sulphate group is dominated